AKUNTABILITAS DAN TRANSPARANSI PEMERINTAH DESA DALAM PENGELOLAAN ALOKASI DANA DESA DI DESA BONGKARAS KECAMATAN SILIMA PUNGGA-PUNGGA, KABUPATEN DAIRI”. - Parhusip, Poltak Teodorus; Girsang, Christy (Jurnal Riset Akuntansi & Keuangan, 2023)
The purpose of this study is to analyze the Accountability and Transparency of village fund allocation management in Bongkaras Village. The formulation of the problem in this study is "Why is the Village Fund Allocation in Bongkaras Village, Silima Pungga-Pungga District, Dairi Regency not yet Accountability and Transparency? The population in this study is the Budget and Realization of Village Fund Allocation. The sample is part of the population, where the sample used is data on the Allocation of Village Funds in Bongkaras Village in 2015-2019. The data needed is primary data using question and answer interviews and secondary data using documentation techniques  From the results of this study, it shows that in the Management of Village Fund Allocation in Bongkaras Village as a whole starting from Accountability and Transparency, it has not been carried out properly where the village government only involves the community in the planning and implementation stages but in the responsibility, the community is less involved so that there is a lack of community trust in the village government and there are still many limitations of the community in obtaining information about cash in and cash out and there is no notice board regarding the activities that are being carried out, especially regarding the Management of Village Fund Allocations.